Frequency of Semen Collection Affects Ram Sperm Cryoresistance - Cristina Palacin-Martinez; Mercedes Alvarez; Rafael Montes-Garrido; Marta Neila-Montero; Luis Anel-Lopez; Paulino de Paz; Luis Anel; Marta F. Riesco (Animals, 2022)
The improvement of frozen-thawed sperm quality has been mostly approached from the view of cryopreservation protocol optimization in terms of cryoprotectant solutions, freezing-thawing rates and antioxidant supplementation, while the impact of sperm collection frequency remains unknown in rams. In this work, a multiparametric study was carried out in cooled and frozen-thawed semen to evaluate sperm quality after different semen collection frequencies during a month: zero sperm collection (0 CW), four sperm collections per week (4 CW), and ten sperm collections per week (10 CW). Traditional analyses have been applied, in combination with novel technologies related to redox balance. Frozen-thawed semen quality showed a significant decrease (p < 0.05) in 0 CW and 10 CW in comparison to 4 CW, concerning motility and kinetics parameters. However, apoptosis showed a significant increase (p < 0.05) in 10 CW in comparison to 0 CW and 4 CW. The employment methods related to redox balance provided us with the definitive probe to ensure the influence of collection frequency on balance redox after thawing. Specifically, glutathione peroxidase (GPX) and superoxide dismutase (SOD) activity showed a significant decrease (p < 0.05) in 10 CW compared to 0 CW and 4 CW. The characterization of alternative strategies to sperm cryopreservation based on consideration of male sexual regimes, could improve the quality of frozen-thawed sperm.